2012
DOI: 10.1210/me.2012-1004
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Methylation and Decreased Expression of PDX-1 in Pancreatic Islets from Patients with Type 2 Diabetes

Abstract: Mutations in pancreatic duodenal homeobox 1 (PDX-1) can cause a monogenic form of diabetes (maturity onset diabetes of the young 4) in humans, and silencing Pdx-1 in pancreatic β-cells of mice causes diabetes. However, it is not established whether epigenetic alterations of PDX-1 influence type 2 diabetes (T2D) in humans. Here we analyzed mRNA expression and DNA methylation of PDX-1 in human pancreatic islets from 55 nondiabetic donors and nine patients with T2D. We further studied epigenetic regulation of PDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
192
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 48 publications
13
192
0
1
Order By: Relevance
“…It has even been suggested that changes in methylation could actually represent a consequence-and not a cause-of altered transcriptional activity [27]. In addition, the bead array screens a minor portion of the CpG sites in the genome, and we cannot exclude that other regions, such as enhancer regions, are regulatory important for gene expression [28]. All together, the extent to which the observed changes in DNA methylation in this study affect gene expression over time, in a subset of individuals at risk or during certain specific metabolic challenges remain to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…It has even been suggested that changes in methylation could actually represent a consequence-and not a cause-of altered transcriptional activity [27]. In addition, the bead array screens a minor portion of the CpG sites in the genome, and we cannot exclude that other regions, such as enhancer regions, are regulatory important for gene expression [28]. All together, the extent to which the observed changes in DNA methylation in this study affect gene expression over time, in a subset of individuals at risk or during certain specific metabolic challenges remain to be determined.…”
Section: Discussionmentioning
confidence: 96%
“…Two of the most significant DMRs including 164 and 105 CpG sites were located in PDX1 gene, strongly supporting the previous finding of increased methylation and decreased expression of PDX1 in diabetic islets (Figure 1). Glucose increases Pdx1 methylation in mouse clonal β‐cells,7 and a hyperglycemia‐associated single‐nucleotide polymorphism in PDX1 alters PDX1 methylation status in human islets 8. These findings together show that epigenetic modifications of PDX1 could contribute to the development and pathogenesis of type 2 diabetes.…”
mentioning
confidence: 76%
“…Differentially methylated regions ( DMR s; red bars) and histone modifications (blue bars) are shown around the PDX 1 region on human chromosome 13. PDX 1 expression levels in control participants (Contl), participants with impaired glucose tolerance ( IGT ) and participants with type 2 diabetes (T2D) are shown on the upper left panel 7. Average methylation levels of DMR s of control and type 2 diabetes participants are shown on the upper right panel 3.…”
mentioning
confidence: 99%
“…Human population studies will likely prove invaluable for identifying T2DM susceptibility genes, for drug testing, and for characterization of other aspects of t2DM such as environmental and lifestyle factors. evaluation of epigenetic interactions in glucose regulation can also be studied in T2DM patients (Yang et al, 2012;Volkmar et al, 2012). drugs such as troglitazone, pioglitazone, and rosiglitazone have caused liver disease, myocardial infarctions, and heart failure (Scheen, 2001;Smith, 2003;Taylor and Hobbs, 2009;Nissen and Wolski, 2010).…”
Section: Glucose Biology: Population and Environment Levelmentioning
confidence: 99%